REALISTIC SIMULATION IN PHARMACEUTICAL EDUCATION: : FROM THEORY TO PRACTICE - Pacheco da Silva, Marlúcia (Health and Society, 2021)
Realistic Simulation is a method used to extend or replace real experiences, which promotes the integration of technical skills and theoretical knowledge, stimulating students to coordinate several competences simultaneously. This paper intends to present the theoretical and practical aspects of realistic simulation in pharmaceutical education. A bibliographic search in the Google academic database was carried out selecting 22 articles effectively, by means of search limits from 2007 to May 2017, published in Portuguese and English. Selected articles have demonstrated that realistic simulation in pharmaceutical education is growing rapidly, mainly related to patient care and safety. As benefits in the teaching-learning process, the interactivity and active participation of students in a safe and realistic environment, without risks to the patient, with increased safety and clinical decision-making capacity, as well as the development of psychomotor and cognitive competencies for care in health. Realistic simulation does not replace in-service teaching, but complements the practice of structured and guided reflection that contributes to personal and professional growth.